(3QSGdI GHf SjfG Edi CHj GdMSf Sgd Hf eMeO GdSgjdj aj CeQ eSJhQ GdUfYIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI bGd LQj Hjfj hHjf GdTjN GdSjO GdaUd GdChd ai GdCeG dcdj dgPg GdUfGYI COeJ GdfXQ ai GdCehQ GdWHjYjI s
(3BNQgG (B:s
(3GdaUd GdJGSY ai JeGe GdYed gPG GdEcSjQ jUHZ daSN hjZhU HOgfg hjdfJ HcdSg s
(3Vef eLehY , JQJjHgG (B: 2s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs